Socialization and Counseling on the Dangers of Drugs in Dayah Mini Aceh - Riyaldi, Muhammad Haris; Halim, Hendra; Firdaus, Mohd; Syahrizal, Teuku Muhammad; Faisal, Faisal; Darwanis, Darwanis; Murkhana, Murkhana; Jamal, Abd. (Jurnal Pengabdian Bakti Akademisi, 2024)
The primary aim of this international community service activity was to enhance the understanding and awareness of the dangers of drug abuse among the students of Dayah Mini Aceh. The service learning (SL) method was employed, involving active participation and engagement from the community. The activity took place on Saturday, May 25, 2025, at Dayah Mini Aceh, located in Kecamatan Syiah Kuala, Banda Aceh. The speakers included Mohd Firdaus from JAKIM, Hendra Halim, M.E., and Teuku Muhammad Syahrizal, M.Ag. from Universitas Syiah Kuala. Twenty Dayah students participated in the event. Data was collected through questionnaires, observations, and interviews and was analyzed using both qualitative and quantitative descriptive methods. The results indicated a significant increase in the students' understanding of drug dangers, with the average score rising from 60% before the activity to 85% after. Additionally, the participants' awareness and commitment to avoiding drug use improved from 50% to 90%. These findings suggest that the service-learning method effectively enhances drug awareness and prevention knowledge among the target community. This activity not only met its objectives but also contributed to achieving the Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being) and SDG 16 (Peace, Justice, and Strong Institutions). The successful implementation of this activity highlights the potential of similar approaches in other community service initiatives aimed at drug prevention and education.